PARP2 controls double-strand break repair pathway choice by limiting 53BP1 accumulation at DNA damage sites and promoting end-resection. Issue 21 (3rd October 2017) - Fouquin, Alexis; Guirouilh-Barbat, Josée; Lopez, Bernard; Hall, Janet; Amor-Guéret, Mounira; Pennaneach, Vincent
Abstract: Double strand breaks (DSBs) are one of the most toxic lesions to cells. DSB repair by the canonical non-homologous end-joining (C-EJ) pathway involves minor, if any, processing of the broken DNA-ends, whereas the initiation of DNA resection channels the broken-ends toward DNA repair pathways using various lengths of homology. Mechanisms that control the resection initiation are thus central to the regulation to the choice of DSB repair pathway. Therefore, understanding the mechanisms which regulate the initiation of DNA end-resection is of prime importance. Our findings reveal that poly(ADP-ribose) polymerase 2 (PARP2) is involved in DSBR pathway choice independently of its PAR synthesis activity. We show that PARP2 favors repair by homologous recombination (HR), single strand annealing (SSA) and alternative-end joining (A-EJ) rather than the C-EJ pathway and increases the deletion sizes at A-EJ junctions. We demonstrate that PARP2 specifically limits the accumulation of the resection barrier factor 53BP1 at DNA damage sites, allowing efficient CtIP-dependent DNA end-resection. Collectively, we have identified a new PARP2 function, independent of its PAR synthesis activity, which directs DSBs toward resection-dependent repair pathways.